Pre-School Children’s Possibility of Enhancing Learning Motivation in the Process of Learning Violin - Isakova, Jelena; Bernāts, Guntars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Motivation has always been an essence of human actions derived from each individual’s goals, needs , interests, abilities, etc. Motivation formes from an early age, when a child starts to unerstand that something is necessary, important, and that he has to act to satisfy the need. Pre-school age group children are interested in surrounding world regarding new knowledge and skills which can be obtained and developed, therefore, by observating this age group, parent’s and/or teacher’s first steps in cognition and promotion of child’s learning motivation are taken.Promoting children’s motivation to learn during educational process is one of the most pressing pedagogical issues, especially nowadays when child loses primary desire to learn and explore under the influence of tehnology and widely available information resources. Therefore the issue of promoting learning motivation in pre-school age was designated to reasearch, because this is the period when the foundation of the whole future life is laid – considering learning, defining objectives and achieving goals.The objective of this research to explore pre-school children's possibility of enhancing learning motivation in the process of learning violin.